Old-school comfort food ebook The way i learned to cook. - Guarnaschelli, Alex (2013)
How does one become an Iron Chef and a Chopped judge on Food Network—and what does she really cook at home? Alex Guarnaschelli grew up in a home suffused with a love of cooking, where soufflés and cheeseburgers were equally revered. The daughter of a respected cookbook editor and a Chinese cooking enthusiast, Alex developed a passion for food at a young age, sealing her professional fate. Old-School Comfort Food shares her journey from waist-high taste-tester to trained chef who now adores spending time in the kitchen with her daughter, along with the 100 recipes for how she learned to cook—and the way she still loves to eat. Here are Alex’s secrets to great home cooking, where humble ingredients and familiar preparations combine with excellent technique and care to create memorable meals. Alex brings her recipes to life with reminiscences of everything from stealing tomatoes from her aunt’s garden and her first bite of her mother’s pâté to being one of the few women in the kitchen of a renowned Parisian restaurant and serving celebrity clientele in her own successful New York City establishments. With 75 color photographs and ephemera, Old-School Comfort Food is Alex’s love letter to deliciousness.